1992
DOI: 10.1142/s0217984992000223
|View full text |Cite
|
Sign up to set email alerts
|

X-RAY-IRRADIATED KTiOPO4: ESR STUDIES

Abstract: The study of radiation paramagnetic centres (RPC) arising in flux-grown KTiOPO 4 (KTP) single crystals at X-ray-irradiation at 300 K was conducted by the ESR-method in the temperature range of 3.7÷300 K . For the first time in X-ray-irradiated KTP there were found electron and hole RPC stable at room temperature and related to Ti 3+ and Al 3+ impurity, respectively.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
7
0

Year Published

1995
1995
2015
2015

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(8 citation statements)
references
References 0 publications
1
7
0
Order By: Relevance
“…B. Andreev and V. Efimov [ 11 ] observed an aluminum-related paramagnetic hole center, the Ti 3+ centers previously reported by M. G. Roelofs [6] and an oxygen hole center. J.-T. Yu et al [12] studied the oxygen hole center O-produced in Al-doped KTP crystals by the ),-irradiation at room temperatures.…”
Section: Introductionmentioning
confidence: 59%
“…B. Andreev and V. Efimov [ 11 ] observed an aluminum-related paramagnetic hole center, the Ti 3+ centers previously reported by M. G. Roelofs [6] and an oxygen hole center. J.-T. Yu et al [12] studied the oxygen hole center O-produced in Al-doped KTP crystals by the ),-irradiation at room temperatures.…”
Section: Introductionmentioning
confidence: 59%
“…The oxygen vacancy concentration is mainly determined by the annealing temperature in comparison with the annealing time and concentration of H 2 . The oxygen vacancies are located from O(1) to O (8). Under high temperatures and low oxygen conditions, oxygen ions diffuse from the interior to the surface.…”
Section: Discussionmentioning
confidence: 99%
“…The cause of gray tracks has been attributed to Ti 3+ centers. [3][4][5][6] Ti 3+ centers related to gray tracks can be produced by an electric field, 4 annealing in hydrogen atmosphere, 6,7 X-ray irradiation, 8,9 or an intense laser beam. 10 To the best of our knowledge, no systematic studies on the reaction mechanism of hydrogen treatment at high temperature have been reported.…”
Section: Introductionmentioning
confidence: 99%
“…Shf structure of their EPR lines is due to the interaction with the nearest nuclear spin I = 5/2 and most probably it is the trivalent aluminum Al" (EPR of hole defects with and without neighboring A1 3 + ion was observed in KTP previously [13][14][15][16]). An additional splitting of the EPR lines from these Al-related hole defects in RTP for some orientations of the magnetic field H is due to phosphorus nucleus 31 P. These S = 1/2 point defects can be identified as holes trapped by a titanyl oxygen with nearby Al impurity ion located at or near a Ti site [16].…”
Section: Discussionmentioning
confidence: 99%
“…6 (dashed line). The first pair of equivalent nuclei (splitting factor a 3 = 3.7 Oe) can be identified as the pair of 31 P by the analogy to KTP [13] where two different phosphorus were detected in flux-grown KTP with use of the ENDOR. The second pair of nuclei (splitting factors a 2 = 6.3 Oe and a 1 = 8.5 Oe, correspondingly), responsible for the shf structure of the para -m a g n e t i c c e n t e r I I I , c o u l d b e a s c r i b e d a s t h e p a i r o f i n e q u i v a l e n t 31 P nuclei or as 31 P and 1 H together.…”
Section: Discussionmentioning
confidence: 99%